Combining PD-1 Inhibitor with VEGF/VEGFR2 Inhibitor in Chemotherapy: Report of a Patient with End-Stage Cholangiocarcinoma and Review of Literature - Ma, Zhenjiang; Li, Heping; Liu, Liangshuai (Recent Patents on Anti-Cancer Drug Discovery, 2021)
Background: Cholangiocarcinoma is the second-largest liver cancer, and develops from the biliary epithelium, where it discretely progresses. Unfortunately, many patients miss the opportunity of performing surgery when diagnosed with cholangiocarcinoma, and due to its chemotherapeutic insensitivity, its control has always been considered difficult. Objective: Here, we present a case of stage 4 cholangiocarcinoma being controlled by the combination of chemotherapy with PD-1 and VEGF/VEGFR2 inhibitors. Case Presentation: The patient is a 58-year-old male who was diagnosed with a progressed cholangiocarcinoma 2 years ago. From the beginning, metastases were discovered in multiple places, and the patient was unsuccessfully treated with 3 chemotherapy regimens. Therefore, a new therapeutic method was considered, and that involved the testing of a new combination of chemotherapy with PD-1 and VEGF/VEGFR2 inhibitors. Results: After 6 courses of treatment with this combination, the patient’s lesions became smaller and stable. Conclusion: Our case highlights the possibility of combining chemotherapy with PD-1 and VEGF/ VEGFR2 inhibitors for the treatment of cholangiocarcinoma patients. This combination may herald new hope for patients who run out of regimens.
Keywords: VEGF/VEGFR2